PTU-061 Immunotherapy-related gastritis in a tertiary oncology centre. (June 2019) - Cheung, Vincent; Gupta, Tarun; Ye, Weiyu; Middleton, Mark; Fairfax, Ben; Payne, Miranda; Brain, Oliver
Abstract : Introduction: Checkpoint inhibitor immunotherapy use has increased significantly over recent years with licensing for more indications. Whilst immunotherapy-related colitis and hepatitis are well-recognised adverse events, immunotherapy-related gastritis (irG) is less well-described and can present a diagnostic challenge. Methods: A retrospective review of the oncology/electronic patient records was done to identify irG patients with demographics, cancer and immunotherapy type, investigations and treatments recorded. Results: From Jan 2014 to Dec 2018, 11 of 205 patients (5.4%) receiving immunotherapy for melanoma had histologically confirmed irG. Median age of patients with irG was 64 with mean 58 (cohort median 66, mean 63). All patients had oncological response to immunotherapy radiologically at time of gastritis. The predominant symptom was anorexia (100%) then nausea or weight loss (82%, 9/11) then fatigue (64%, 7/11). Median weight loss was 5 kg (mean 8.1 kg). Median time to symptoms was 323 days (mean 277). Table 1 below shows the features of the patients. The characteristic endoscopic appearance of irG was of diffuse erythematous/oedematous mucosa ± frank ulceration. 45% of patients had concurrent duodenitis. The main histological pattern was an acute gastritis with a dense, mixed inflammatory infiltrate with crypt abscesses within attenuated crypts and intraepithelial lymphocytosis. The 4 PPI-responsive patients had prior immunotherapy-related diarrhoea/colitis (3) and nephritis (1) treated with steroids. 6 patients required steroids. One had infliximab after two steroid courses failed to control symptoms (4 doses). One patient required a 3 day hospital stay. 3 patients had repeat OGDs showing histological resolution including infliximab patient. Conclusions: While immunotherapy-related colitis usually occurs at week 7, our data suggest that symptomatic irG occurs much later. Given the constitutional symptoms of weight loss and anorexia observed in irG overlap with those commonly seen in cancer, it is probable that irG occurs more frequently than our data suggest. Moreover, such presenting features of gastritis almost certainly contributes to the observed delay in diagnosis. Some patients may respond to PPI alone if they have had other immunotherapy-related adverse events treated with steroids before. First line irG treatment is usually steroids, and infliximab may be useful if steroid-refractory. Early liaison with gastroenterology team to facilitate timely endoscopy and biopsy is paramount.